What Is the Problem With Sexual Intimacy Following Intimate Partner Violence in the DSM-5?. (February 2022) - Buller, Alannah; Epstein, Sarah; Hosken, Norah
Drawing on a data subset from a larger Australian-focused project, this article reports on the ways that women's voices have been silenced and misrecognized in the representation of the impact on sexual intimacy following experiences of intimate partner violence. Bacchi's "What Is the Problem Represented to Be?" approach was used to identify, explore and unpack the "problem" representations of the impacts on sexual intimacy following women's experiences of intimate partner violence within the Diagnostic and Statistical Manual of Mental Disorders.